Environmental Planning and Modeling - Madu, Christian N. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The focus of this reprint is on environmental planning and modeling. It examines articles on green consumption, biodiversity, and household waste recycling, as well as presenting a review of the trend in publications on household waste recycling. A number of country-based applications are presented and models are used to show how multiple perspectives can be considered in policy making. This reprint will be of special interest to researchers and readers involved in sustainability management. Further, although some chapters present models to solve sustainability problems, they also share policy and decision-making frameworks for applying such models.